Validation of the Brain Symptom and Impact Questionnaire (BASIQ) to assess symptom and quality of life in brain metastases. (July 2014) - Bedard, Gillian; Ray, Saurabh; Zhang, Liying; Zeng, Liang; Cella, David; Wong, Erin; Danjoux, Cyril; Tsao, May; Barnes, Elizabeth; Sahgal, Arjun; Holden, Lori; Lauzon, Natalie; et al.
SUMMARY : Objective: To validate the Brain Symptom and Impact Questionnaire (BASIQ) version 1.0 for brain metastases.Methods: Patients with brain metastases and their healthcare professionals (HCPs) assessed the relevance of the BASIQ on a 0–10 scale with 10 as extremely relevant.Results: A total of 52 patients and 20 HCPs participated in this study. In total, 95% of HCPs and 85% of patients found all items relevant. Balance and walking ability were rated relevant by 100% of patients and HCPs. Headache, nausea, energy, memory and ability to do housework were also rated relevant by 100% of HCPs. Over 95% of patients determined the items of ability to do housework, tiredness, energy, vision, memory and putting ideas into words as relevant. There were no items rated below 7 by patients or below 5 by HCPs.Conclusion: This study indicates that BASIQ version 1.0 has valid content items encompassing disease-related symptom and impact on daily living.